1998
DOI: 10.1046/j.1365-2168.1998.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the anatomical distribution of venous reflux with clinical symptoms and venous haemodynamics in primary varicose veins

Abstract: Patients at high risk of developing complications of venous disease may be identified by an accurate non-invasive evaluation of reflux patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 25 publications
2
26
1
1
Order By: Relevance
“…5,6,10,18,19 Another study with a patient population of women with C2 disease demonstrated a prevalence of 60% with GSV reflux only, and 17% with SSV reflux only. 20 Currently, there is no explanation for this significant difference in prevalence.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…5,6,10,18,19 Another study with a patient population of women with C2 disease demonstrated a prevalence of 60% with GSV reflux only, and 17% with SSV reflux only. 20 Currently, there is no explanation for this significant difference in prevalence.…”
Section: Discussionmentioning
confidence: 95%
“…Our findings indicated that saphenous vein du- [2] Varicosity off the GSV at the knee, [3] Segmental hypoplasia of the GSV at the level of the varicosity, [4] Normal GSV below the hypoplastic segment with varicose tributaries). b, Varicosities of the small saphenous vein (SSV) ([1] GSV, [2] tortuous SSV, [3] cranial or dorsal extension of SSV, [4] medial gastrocnemial vein, [5] common trunk of SSV with gastrocnemial veins, [6] popliteal vein, [7] communicating vein of the calf between the SSV and GSV). Courtesy of Dr Jean-Francoise Uhl. plication is rare and is not associated with the severity of CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of reflux in the SFJ, according to the studies reviewed, is between 53% and 89.8%. [1][2][3]8,[16][17][18][19][20] We have noted that finding reflux in the groin does not imply that it originates at that point, as reflux from the pelvis or abdominal wall can also cause primary VVs (SFJ reflux, 41.9% and competent SFJ with reflux from proximal veins, 35.4%). We also noted that analyzing only the presence of reflux in the SFJ of the GSV would miss 10.9% of limbs of reflux in the SFJ of the AAGSV.…”
Section: Discussionmentioning
confidence: 98%
“…En cambio, hemos considerado VP de reentrada a aquella que presenta un fl ujo anterógrado en diástole mucho mayor que el fl ujo retrógrado en sístole. Varios trabajos 28,33,36,46 publican la mayor frecuencia de las VP insufi cientes en la pierna con respecto al muslo, pero desde nuestro punto de vista, creemos que podrían corresponder, en su gran mayoría, a puntos de reentrada.…”
Section: Sistema De Venas Perforantesunclassified